2015
DOI: 10.7759/cureus.422
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Hypertensive Retinopathy with Mean Platelet Volume Among Hypertensive Patients

Abstract: Background The pathophysiological mechanism of hypertensive retinopathy (HR) is not fully understood, although it is thought that increased platelet activation may have a pivotal role. This study was designed to investigate this possibility by determining the frequency and magnitude of mean platelet volume (MPV), a marker of platelet activation, in HR.Methods One hundred and thirty-eight patients, aged 31 to 80 years, who had essential hypertension with HR were enrolled in the study. The patients who presented… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 24 publications
3
6
0
Order By: Relevance
“…Bhatti et al observed that MPV was elevated in hypertensive retinopathy and that a between elevated MPV and various grades of hypertensive retinopathy [7]. Similar findings were observed by Hussain et al & Yadav et al [2,8].…”
Section: Introductionsupporting
confidence: 64%
“…Bhatti et al observed that MPV was elevated in hypertensive retinopathy and that a between elevated MPV and various grades of hypertensive retinopathy [7]. Similar findings were observed by Hussain et al & Yadav et al [2,8].…”
Section: Introductionsupporting
confidence: 64%
“…29 It has also been shown that an increased MPV value is associated with several ocular vascular diseases such as retinal artery occlusion, diabetic retinopathy, and hypertensive retinopathy. [30][31][32] Sahin et al 32 found a significant increase in the MPV values in patients with retinal artery occlusion and in another study they found an increased MPV in patients with NAION. 33 Although both the MPV and PDW are markers of platelet activation, Vagdatli et al 34 showed that the PDW seems to be a more specific marker of platelet activation than the MPV, which was not found to be elevated during single platelet distension caused by platelet swelling.…”
Section: Discussionmentioning
confidence: 94%
“…MPV has been found to be significantly higher in obese than in non-obese individuals, and an elevated MPV is associated with an increased risk of acute myocardial infarction [2,3]. In addition, in patients with hypertensive retinopathy, an elevated MPV was shown to correspond with increased severity of retinopathy [16]. Hs-CRP levels are used as an immunological marker of CVD risk [7].…”
Section: Discussionmentioning
confidence: 99%